Combining proximate with online learning in real-time: ambidextrous teaching and pathways towards inclusion during COVID-19 restrictions and beyond. Issue 3 (3rd July 2021) - Thomas, Matthew; Bryson, John R.
ABSTRACT: COVID-19 forced universities to engage in rapid improvisation and adoption of online learning and teaching. This paper explores "real-time blended" learning in which online students are taught simultaneously with students who are experiencing proximate learning. Two cliques could develop with those learning online becoming observers rather than participants in an active learning process. This paper is based on action-based research to develop an inclusive approach to simultaneous teaching of proximate and online students. This approach includes alterations in classroom layout, the equipment used, facilitating varying modes of social interaction and the role of communication. Effective teaching requires continual minor modifications to teaching design and delivery. This represents an ambidextrous approach to teaching in which teachers focus on the immediate co-creation of student experiences, but also identify cues which are used to adjust the ways in which they engage with a student cohort over the course of delivering a module. Module evaluation becomes an ongoing process in which alterations are made in real-time and to subsequent learning encounters with students. The paper evaluates student performance and concludes that the approach went some way towards ensuring equality of the student experience between those learning online and those proximate with the lecturer.